Effect of different iron precursors on the synthesis and photocatalytic activity of Fe–TiO2 nanotubes under visible light. Issue 3 (15th February 2020) - Zafar, Zulakha; Ali, Imran; Park, Seongjun; Kim, Jong-Oh
Abstract: Fe–TiO2 nanotubes (Fe-TNTs) were developed to entitled photocatalytic reactions using a visible range of the solar spectrum. This work reports on the effect of different Fe precursors on the synthesis, characterization, kinetic study, material and photocatalytic properties of Fe-TNTs prepared by electrochemical method using three different Fe precursors i.e. (iron nitrate [Fe(NO3 )3 ⋅9H2 O], iron sulfate [FeSO4 ⋅7H2 O], and potassium iron ferricyanide [K3 Fe(CN)6 ]). X-ray diffraction, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and Fourier transform infrared spectroscopy are used to examine the influence of the Fe precursor on the Fe-TNTs material characterization. Different Fe-TNT properties, such as enhanced photoactivity, good crystallization, and composition of titania structures (anatase and rutile) could be acquired from different iron precursors. Among the three iron precursors, Fe(NO3 )3 provided with the only anatase phase, yields the highest photocatalytic activity. Congo red is used as a model compound to check the photocatalytic efficiency of synthesized materials because it has a complex aromatic structure which makes it difficult to be biodegraded or oxidized with the aid of chemicals. The photocatalytic efficiency of all Fe-TNT can be arranged in the following order: TNT-FeN > TNT-FeS > TNT-FeK > TNT. The kinetic rate constant of congo red degradation using the Fe-TNT with Fe(NO3 )3 was 0.44 h −1 with a half-life of 1.57 h −1 Graphical abstract: Image 1 Highlights: Fe-TNT synthesized by several different Fe precursors followed by Fe(NO3 )3, FeSO4, K3 Fe(CN)6 . Different iron precursors have a different effect on material properties. Chemical structure of iron precursors affects the interaction with TNT structure. Photocatalytic activity of the Fe-TNTs followed the order TNT-FeN > TNT-FeS > TNT-FeK > pure TNTs.